The Role of Islamic Religious Education in Nurturing the Spirit of Nationalism Among Students - hilman, Cecep (Al-Ilmu, 2024)
Islamic religious education has a strategic role in shaping the character of a moral and ethical nation, as well as strengthening the spirit of nationalism among students. This study aims to explore the contribution of Islamic religious education in fostering national values through a descriptive qualitative approach. The research subjects included 30 informants, including teachers, students, and principals from five junior and senior high schools that have religious education programs integrated with national values. Data were collected through in-depth interviews, observation, and document analysis, then thematically analyzed. The results showed that religious values such as honesty, responsibility, and respect for diversity play a significant role in maintaining social harmony. The national values-based curriculum is a key element in shaping the character of students who are both religious and nationalist. Contextual learning strategies, such as group discussions and hands-on practice, help students understand the relevance of national values in everyday life. Teachers have a central role as facilitators and models of national values, although challenges such as limited time and support remain. This research confirms the importance of Islamic religious education as a bridge between local and global values, capable of producing a generation that is not only faithful but also committed to diversity and national unity